Prenatal diagnosis and molecular cytogenetic characterization of de novo partial monosomy 3p (3p26.3→pter) and partial trisomy 16q (16q23.1→qter) - Chih-Ping Chen; Fung-Yu Hung; Schu-Rern Chern; Peih-Shan Wu; Yen-Ni Chen; Shin-Wen Chen; Chen-Chi Lee; Wayseen Wang (Elsevier, 2016)
Objective: To present the prenatal diagnosis and molecular cytogenetic characterization of a de novo unbalanced reciprocal translocation. Case Report: A 37-year-old woman, G3P1, underwent amniocentesis at 17 weeks of gestation because of her advanced maternal age. Her husband was 38 years old. Amniocentesis revealed a derivative chromosome 3 with the deletion of terminal 3p and the addendum of an unknown extra chromosomal segment on the distal 3p. The parental karyotypes were normal. Prenatal ultrasound findings were unremarkable. Array comparative genomic hybridization (aCGH) analysis using cultured amniocytes revealed a 2.38-Mb deletion in 3p26.3 [arr 3p26.3 (1-2,380,760)×1] encompassing 15 genes, which included 3 OMIM genes CHL1, CNTN6, and CNTN4, and a 13.17-Mb duplication in 16q23.1-q24.3 [arr 16q23.1q24.3 (76,999,082-90,170,596)×3] encompassing 207 genes, which included 81 OMIM genes. The pregnancy was subsequently terminated, and a malformed fetus was delivered with facial dysmorphism. Postnatal cord blood analysis revealed a karyotype of 46,XY,der(3)t(3;16)(p26.3;q23.1)dn. Polymorphic DNA marker analysis by quantitative fluorescent polymerase chain reaction (QF-PCR) on the DNAs extracted from the placenta and parental blood showed a paternal origin of the aberrant chromosome. Conclusion: The aCGH and QF-PCR analyses helped in delineating the genomic imbalance and parental origin of prenatally detected de novo unbalanced reciprocal translocation.